FTO – A Common Genetic Basis for Obesity and Cancer - Lan, Ning; Lu, Ying; Zhang, Yigan; Pu, Shuangshuang; Xi, Huaze; Nie, Xin; Liu, Jing; Yuan, Wenzhen (Frontiers in Genetics, 2020)
In recent years, the prevalence of obesity and cancer have been rising. Since this poses a serious threat to human health, the relationship between the two has attracted much attention. This study examined whether fat mass and obesity-associated (FTO) genes are linked, taking into account a Genome-wide Association Study (GWAS) that revealed multiple single nucleotide polymorphism sites (SNPs) of the FTO gene, indicating an association between obesity and cancer in different populations. FTO proteins have been proved to participate in adipogenesis and tumorigenesis with post-transcriptional regulation of downstream molecular expression or through the target of the mammalian target protein rapamycin (mTOR). FTO inhibitors have also been found to share anti-obesity and anti-cancer effects in vivo. In this review, we comprehensively discuss the correlation between obesity and cancer by measuring FTO gene polymorphism, as well as the molecular mechanism involved in these diseases, emphasizing FTO as the common genetic basis of obesity and cancer.